Strategy and Opportunity for The Development of Duck Breeding Farm - Prasetyo, L Hardy (Indonesian Animal Sciences Society, 2006)
The recent development of duck farming requires the availability of good quality breeding stocks commercially in order to improve productivity and efficiency . Presently, there is no commercial duck breeding farm which can produce good quality breeding stocks . This article presents information on alternatives in developing duck breeding farm, particularly for layer ducks . There are two alternative approaches in duck breeding farms : (1) Group breeding farm, which belongs to duck farmers group, as part of a group production system, and (2) Commercial breeding farm, by an individual private company/Semi-Government Institution in a commercial scale and particularly for export market . A good breeding farm requires appropriate systems for selection and mating of the animals in order to guarantee the quality of the breeding stocks being produced . A breeding farm must be economically and technically feasible as an economic entity, so that economic analysis and marketing must be prepared seriously . Key words: Duck, model, breeding farm